2016
DOI: 10.1111/vde.12347
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and epidemiological characterization of caninePseudomonasotitis using a prospective case‐control study design

Abstract: Genetic homology between otic and environmental isolates is consistent with a waterborne source for some dogs, and cross-contamination with other human and animal members within some households.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Larger studies would be required to look at the relationship between breed characteristics and OE. Prior antimicrobial or anti‐inflammatory therapy may impact the microbiota of these individuals as well, although the impact could not be assessed in the present study due to varied therapeutics used, varied chronicity and the sample size. Concurrent and underlying dermatological disease was not a focus of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Larger studies would be required to look at the relationship between breed characteristics and OE. Prior antimicrobial or anti‐inflammatory therapy may impact the microbiota of these individuals as well, although the impact could not be assessed in the present study due to varied therapeutics used, varied chronicity and the sample size. Concurrent and underlying dermatological disease was not a focus of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the chronic and treatment‐resistant nature of P. aeruginosa infections in dogs, long‐term antimicrobial treatment often is required . However, few studies have assessed antimicrobial resistance in clinical P. aeruginosa isolates from dogs and previous reports have found that the incidence of carbapenem‐nonsusceptible P. aeruginosa isolated from dogs was low . There is a report on carbapenemase‐producing P. aeruginosa from an anal swab of a healthy dog in China, which was highly similar to that from humans in the same area of China .…”
Section: Introductionmentioning
confidence: 99%
“…This could also explain the seasonal pattern that was found in the present study, regarding topical AMU since TAMs are applied in dermatological conditions and in cases of otitis [ 2 , 31 ]. Furthermore, in warmer months, owners and their pets might spend more time outdoors engaging in activities such as swimming in open water, which might predispose dogs for ear infections [ 32 ].…”
Section: Discussionmentioning
confidence: 99%